2012
DOI: 10.1016/j.virol.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Efficient propagation of archetype BK and JC polyomaviruses

Abstract: BKPyV and JCPyV are closely related, ubiquitious human pathogens that cause disease in immunocompromised patients. The DNA sequence of the regulatory regions distinguishes two forms of these viruses, designated archetype and rearranged. Although cell culture systems exist for rearranged BKPyV and JCPyV, currently there is no robust cell culture system to study the archetype viruses. Large T antigen (TAg) is a virally encoded protein required to initiate viral DNA synthesis. Because archetype virus produces und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 44 publications
2
63
0
Order By: Relevance
“…2A). The WT and miRNA mutant viruses were purified from 293TT cells, which allow both archetype virus and rearranged variants to replicate (8). RNA was harvested from infected 293TT cells and Northern blotting confirmed that the mutant virus does not produce its mature 5P and 3P miRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2A). The WT and miRNA mutant viruses were purified from 293TT cells, which allow both archetype virus and rearranged variants to replicate (8). RNA was harvested from infected 293TT cells and Northern blotting confirmed that the mutant virus does not produce its mature 5P and 3P miRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Archetype virus and rearranged variant miRNA mutated viruses were created using site-directed mutagenesis as described in SI Materials and Methods and a list of primers used is presented in Table S1. The WT and mutant viral genomes were transfected into 293TT cells to produce crude lysates (8). Viral stocks were expanded in 293TT cells and purified by density centrifugation on Cesium chloride gradients (30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, BK polyomavirus may be reactivated when the immune system is suppressed. 7 Virus reactivation is a main complication after renal transplant, inducing BK virus-associated nephropathy (BKVAN). [4][5][6]8 BK virus-associated nephropathy is characterized by inflammatory interstitial nephropathy.…”
Section: Introductionmentioning
confidence: 99%